Obtaining Salt Stress-Tolerant Eggplant Somaclonal Variants from In Vitro Selection - Sami Hannachi (MDPI AG, 2021)
An efficient regeneration protocol was applied to regenerate shoots on salt stress-tolerant calli lines of aubergine (Solanum melongena). These NaCl-tolerant cell lines were obtained by two different methods. On the one hand, the developed callus tissue was transferred to a medium with a continuous salt content of 40, 80, 120, or 160 mM NaCl. On the other hand, the callus tissue was subjected to a stepwise increasing salinity to 160 mM NaCl every 30 days. With the second method, calli which could be selected were characterized by compact growth, a greenish color, and absence of necrotic zones. When grown on salt-free medium again, NaCl-tolerant calli showed a decline in relative growth rate and water content in comparison to the control line. This was more obvious in the 120 mM NaCl-tolerant callus. Lipid peroxidase activity increased in 40 and 80 mM NaCl-tolerant calli; yet did not increase further in 120 mM-tolerant callus. An increase in ascorbic acid content was observed in 80 and 120 mM NaCl-tolerant calli compared to the 40 mM NaCl-tolerant lines, in which ascorbic acid content was twice that of the control. All NaCl-tolerant lines showed significantly higher superoxide dismutase (SOD) (208–305–370 µmol min−1 mg−1 FW) and catalase (CAT) (136–211–238 µmol min−1 mg−1 FW) activities compared to control plants (231 and 126 µmol min−1 mg−1 FW). Plants were regenerated on the calli lines that could tolerate up to 120 mM NaCl. From the 32 plants tested in vitro, ten plants with a higher number of leaves and root length could be selected for further evaluation in the field. Their high salt tolerance was evident by their more elevated fresh and dry weight, their more increased relative water content, and a higher number and weight of fruits compared to the wild-type parental control. The presented work shows that somaclonal variation can be efficiently used to develop salt-tolerant mutants.